2019
DOI: 10.1126/sciadv.aax4215
|View full text |Cite
|
Sign up to set email alerts
|

Directed aging, memory, and nature’s greed

Abstract: Disordered materials are often out of equilibrium and evolve very slowly. This allows a memory of the imposed strains or preparation conditions to be encoded in the material. Here we consider "directed aging", where the elastic properties of a material evolve in the direction defined by its aging history. The evolution to a lower-energy configuration is controlled by steepest decent and affects stressed regions differently from unstressed ones. This process can be considered to be a "greedy algorithm" of Natur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 43 publications
2
61
0
Order By: Relevance
“…1A), which is naturally multistable. Our analysis can be generalized to other disordered mechanical systems, such as elastic networks (16), that are also generically multistable. It was previously shown that creased sheets, such as those of self-folding origami, can be folded into exponentially many discrete folded structures from the flat, unfolded state (17,18).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1A), which is naturally multistable. Our analysis can be generalized to other disordered mechanical systems, such as elastic networks (16), that are also generically multistable. It was previously shown that creased sheets, such as those of self-folding origami, can be folded into exponentially many discrete folded structures from the flat, unfolded state (17,18).…”
Section: Resultsmentioning
confidence: 99%
“…Other materials can show a plastic change in stiffness in response to aging under strain, such as ethylene vinyl acetate (EVA) foam (36) and thermoplastic polyurethane (37). EVA was used recently (16) to show such behavior in a mechanical system trained for auxetic response. Another possible method, explored specifically for origami creases (20), controls the crease width (and, hence, stiffness) using photolitography (38).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our framework can also be implemented on much larger length scales using recent experimental demonstrations of plasticity in EVA (Ethylene-vinyl acetate) foam [38]. Here, learning involves continually changing the stiffness of existing bonds, rather than growing new bonds every time.…”
Section: Experimental Realizationsmentioning
confidence: 99%
“…(b) EVA foam-based network changes nonlinear elastic properties when aged under strain (adapted from Ref. [38]). (c) Reversible stress softening in actin networks, a natural form of elastic nonlinearity in grown networks (adapted from Ref.…”
Section: Figmentioning
confidence: 99%